DINAMIKA LEKSIKON KE-PARE-AN SAWAH DALAM GUYUB TUTUR SUNDA: KAJIAN EKOLINGUISTIK - Lien Darlina; Wahyuning Dyah (Jurnal Ilmiah Global Education, 2023)
This paper examines the dynamics of lexicons ‘bitter gourd fields’ in Sundanese speech focusing on two problems; (1) How is the language form of lexicon ‘bitter gourd fields’ in Sundanese speech? and (2) How is the dynamics of lexicon ‘bitter gourd fields’ in Sundanese speech? This study applies ecolinguistic theory, and is a descriptive study with qualitative and quantitative approaches. There are two types of data: primary and secondary data. The primary data source is Sundanese speakers who live in Sumedang regency, and as a sample of study, key informants are those above 55 years old and teenagers among 15- 18 years old, and the secondary data are documents related to this study. Data were collected through observation, interview, questionnaire and documentation. The result shows that lexicon ‘bitter gourd fields’ in Sundanese speech of Sumedang regency is grouped based on entities reality of keparean sawah (bitter gourd fields). There are 149 lexicon which are classified into 74 nouns, 74 verbs, and 1 adjective. The dynamics of bitter gourd fields in Sundanese speech, there are 78 lexicons still surviving, while 71 others are less known. It happens due to the influence of many factors and shifts in people’ knowledge and beliefs.